Islam, Bangsamoro and Democracy - Rasul-Bernardo, Amina (Philippine Journal of Public Administration, 2019)
Despite its potential for growth and development, the Bangsamoro region has seen decades of demographic marginalization, repression, and underdevelopment. These social problems, which were attributed to colonialization, are further aggravated by armed conflict between rebel groups and the government, and weak legal framework for regional autonomy. In her speech, Amina Rasul-Bernardo argues that the Bangsamoro conflict can only be addressed with a better understanding of its history and context. Rasul-Bernardo urges the passage of a Bangsamoro Basic Law that strengthens regional autonomy and ensures genuine, sustainable development in the region.
Keywords: Bangsamoro conflict, Bangsamoro history, regional autonomy